2021
DOI: 10.1111/os.12894
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Characteristics and Biomechanical Changes of Lower Lumbar Facet Joints Under Different Loads

Abstract: Objective To explore the kinematic biomechanical changes and symmetry in the left and right sides of the facet joints of lumbar spine segments under different functional loads. Methods Participants (n = 10) performing standing flexion and extension movements were scanned using computed tomography (CT) and dual fluoroscopy imagine system. Instantaneous images of the L3–S1 vertebrae were captured, and by matching a three‐dimensional CT model with contours from dual fluoroscopy images, in vivo facet joint movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, 3D anatomical measurements of the FJ orientation have not been reported in the Chinese population. Furthermore, kinematic characteristics in the different activities of the FJ of the lumbar spine have been less frequently reported, and past studies have focused on the different movements in the standing position (12,19,24). Sitting is as common a physiological position as standing in daily life; however, the kinematic changes of FJ in the sitting position have not been studied extensively.…”
Section: Discussionmentioning
confidence: 99%
“…However, 3D anatomical measurements of the FJ orientation have not been reported in the Chinese population. Furthermore, kinematic characteristics in the different activities of the FJ of the lumbar spine have been less frequently reported, and past studies have focused on the different movements in the standing position (12,19,24). Sitting is as common a physiological position as standing in daily life; however, the kinematic changes of FJ in the sitting position have not been studied extensively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on lumbar facet joint motion are mostly based on the standing position. Song et al [ 21 ] performed related studies on facet joint motion in the standing position and concluded that there was no significant difference in displacement under different weight loads in different segments. Our study found that at 0 kg, the left and right (X axis) and anterior and posterior (Y axis) displacements between L3-4 and L4-5 and the vertical displacement (Z axis) between L3-4 and L4-5 were also smaller than those studied by Song et al, while at 10 kg, the left and right (X axis) and anterior and posterior (Y axis) displacements between L3-4 and L4-5 were relatively smaller than those studied by Song et al, while the vertical displacement (Z axis) was larger.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on lumbar facet joint motion are mostly based on standing position. Song et al (21) made related studies on facet joint motion in standing position and concluded that there was no statistical difference in displacement under different weight loads in different segments. Our study found that, in 0kg, the left and right (X-axis) and anterior and posterior (Y-axis) displacement between L3-4 and L4-5, and the vertical displacement (Z-axis) between L3-4 and L4-5 were also smaller than those studied by Song et al, while in 10kg, the left and right (X-axis) and anterior and posterior (Y-axis) displacement between L3-4 and L4-5 were relatively smaller than those studied by Song et al, while the vertical displacement (Z-axis) was larger.…”
Section: Discussionmentioning
confidence: 99%